Developing Interdisciplinary Error Analysis Teaching Materials Integrating Linguistic and Islamic Values - Kholid, M Ridho; K, M Fikri Nugraha; Arizandy, Aan (English Education: Jurnal Tadris Bahasa Inggris, 2024)
Error Analysis (EA) plays a pivotal role in language education, yet students often perceive it as tedious and challenging. This study addresses this issue by developing innovative EA teaching materials that merge linguistic theory with Islamic values, reflecting the Integrative-Prismatic paradigm unique to Universitas Islam Negeri (UIN) Raden Intan Lampung. Employing the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model within a Research and Development (R&D) framework, this research focuses on the first three stages: Analysis, Design, and Development. Data were collected through comprehensive questionnaires distributed to third-semester students and English Language Education program lecturers. The needs analysis revealed a strong demand for engaging and contextually relevant materials. Consequently, five thematic chapters were developed, each integrating theoretical insights with practical applications and Islamic perspectives. Expert validation confirmed the materials' relevance and quality, leading to further refinements. The findings indicate a significant potential for these interdisciplinary materials to transform EA education by making it more engaging and culturally resonant. This approach enhances linguistic understanding and enriches students' educational experience by aligning with their cultural and religious contexts. Future research will focus on the implementation and evaluation phases to assess the practical impact of these materials on student learning outcomes